1996
DOI: 10.1152/ajplung.1996.270.6.l941
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of xanthine dehydrogenase and xanthine oxidase activity by hypoxia

Abstract: The present study determined the effect of hypoxia on xanthine dehydrogenase (XDH) and xanthine oxidase (XO) activity and gene and protein expression in cultured bovine aortic endothelial cells (BAEC). BAEC were exposed to hypoxia (3% O2) or anoxia (0% O2) for 24 or 48 h and to 24 h of hypoxia followed by 24 h of reoxygenation. Hypoxia- and anoxia-exposed BAEC demonstrated a greater than twofold increase in XDH/XO activity at 24 and 48 h compared with timed controls. Hypoxic cells that were subsequently reoxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 27 publications
2
48
1
Order By: Relevance
“…We found that hypoxia-mediated XDH/XO activation is dependent on the JAK/ STAT pathway in primary cultures of LMVEC. We demonstrated that the XDH/XO activity significantly increased by hypoxia, consistent with the increased phosphorylation or activation of XDH/XO in response to hypoxia in other cells (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). Interestingly, our data demonstrated that XDH/XO activation induced by could be inhibited by either depletion of IL6 using IL6 antibodies, pretreatment with the JAK2 inhibitor AG490 or transient expression of the JAK-STAT pathway blocker SOCS3 and their inhibitory effect on the XDH/XO activation was at a similar magnitude.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that hypoxia-mediated XDH/XO activation is dependent on the JAK/ STAT pathway in primary cultures of LMVEC. We demonstrated that the XDH/XO activity significantly increased by hypoxia, consistent with the increased phosphorylation or activation of XDH/XO in response to hypoxia in other cells (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). Interestingly, our data demonstrated that XDH/XO activation induced by could be inhibited by either depletion of IL6 using IL6 antibodies, pretreatment with the JAK2 inhibitor AG490 or transient expression of the JAK-STAT pathway blocker SOCS3 and their inhibitory effect on the XDH/XO activation was at a similar magnitude.…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that hypoxia activates XDH/XO, an important source of reactive oxygen species (ROS) (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). However, the molecular mechanism underlying the hypoxia-mediated activation of XDH/XO remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, the enzyme xanthine oxidoreductase (XOR) exists primarily in its dehydrogenase form, serving as the rate-limiting step in purine degradation to uric acid. Under conditions of tissue hypoxia (53), ATP is broken down to the purine hypoxanthine, a substrate for XOR, and reversible oxidation or irreversible proteolytic cleavage (17,54), which converts XOR to an oxidase form that can produce large quantities of ROS, including O 2 •Ϫ and its dismutation product, hydrogen peroxide (H 2 O 2 ). In adults, increased vascular O 2 •Ϫ production during chronic exposure to hypoxia has been attributed in major part to XO, which has been found to adversely impact endothelial function by impairing nitric oxide (NO) signaling (26) and to directly contribute to experimental pulmonary vascular remodeling (25).…”
mentioning
confidence: 99%
“…Hypoxia has been reported to increase XOR activity in cultured rat and bovine endothelial cells (11,28,38,39). The mechanism of the increase, however, is uncertain, because some studies have reported increases in XOR mRNA transcript levels (11,39), whereas another study failed to show any alterations in XOR gene expression by hypoxia (28).…”
mentioning
confidence: 99%
“…The mechanism of the increase, however, is uncertain, because some studies have reported increases in XOR mRNA transcript levels (11,39), whereas another study failed to show any alterations in XOR gene expression by hypoxia (28). Furthermore, phosphorylation of XOR in hypoxia has been suggested to account for increased XOR activity (21).…”
mentioning
confidence: 99%